Case report: Unique ultrasound feature of thyroid metastases in occult breast cancer - Zhang, Kaining; Yu, Yong; Zang, Yichen; Xu, Hua; Lv, Beibei; Wang, Qian (Frontiers in Oncology, 2022)
Occult breast cancer is an uncommon type of breast cancer. Metastases of occult breast cancer to other tissues are rather rare. We present a rare case of thyroid metastases in a 46-year-old woman who underwent occult breast cancer. The first ultrasound (US) examination of the thyroid showed that the left lobe was enlarged but had normal thyroid function. At first, this case was misdiagnosed as thyroiditis based on the thyroid US features. However, the cytological and histological results showed that nests of the neoplastic cells were found. Further immunohistochemistry results confirmed that these neoplasms were derived from breast tissue. Analysis using the successive US scans revealed that the sizes and echo of the thyroid repeatedly changed after the radiotherapy and chemotherapy treatment. To our knowledge, this is the first reported case of occult breast carcinoma presenting with thyroid metastases. This case can easy to be misdiagnosed as thyroiditis due to the metastasis area not manifesting as regular suspicious nodules or diffused punctate calcifications. Keywords: Ultrasound; thyroid metastases; occult breast cancer; thyroiditis; case report.